2023
DOI: 10.21203/rs.3.rs-3251626/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between gut microbiota and psoriasis: a bidirectional two-sample Mendelian randomization study

Jin Zhang,
Yang Xiang,
Yingjie Shen
et al.

Abstract: Background: Research has found that the composition of gut microbiota is related to psoriasis and its subtypes. However, the causal effect of gut microbiota on psoriasis is still unclear. Methods: A two sample Mendelian randomization randomized study was conducted using the aggregated statistical data of intestinal microbiota in the meta-analysis of the largest available genome-wide association studies conducted by the MiBioGen Alliance. The summary statistical data for psoriasis, arthropathic psoriasis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
1
Order By: Relevance
“…In line with our findings, Mendelian randomization studies have identified the causal role of microbial taxa for migraine 21 , irritable bowel syndrome 22 and depression 13,23 . Nevertheless, MR studies have indicated the causal role of microbiome in type 2 diabetes 23 , psoriasis 24 , inflammatory bowel diseases 12 and heart failure 25 , which was inconsistent with our findings. However, these inconsistencies can be expected as our approach focuses on the general effects of the microbiome composition, which is more in line with how the FMT studies can inform causality.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with our findings, Mendelian randomization studies have identified the causal role of microbial taxa for migraine 21 , irritable bowel syndrome 22 and depression 13,23 . Nevertheless, MR studies have indicated the causal role of microbiome in type 2 diabetes 23 , psoriasis 24 , inflammatory bowel diseases 12 and heart failure 25 , which was inconsistent with our findings. However, these inconsistencies can be expected as our approach focuses on the general effects of the microbiome composition, which is more in line with how the FMT studies can inform causality.…”
Section: Discussioncontrasting
confidence: 99%